Paper review: An overview on microarray technologies - Fajriyah, Rohmatul (Universitas Ahmad Dahlan, 2021)
Bioinformatics is a branch in Statistics which is still unpopular among statistics students in Indonesia. Bioinformatics research used microarray technology, because data is available through to microarray experiment on tissue sample at hand. Microarray technology has been widely used to provide data for bioinformatics research, since it was first introduced in late 1990, particularly in life sciences and biotechnology research. The emergence and development of the Covid-19 disease further reinforces the need to understand bioinformatics and its technology. There are two of the most advance platforms in microarray technology, namely, are the Affymetrix GeneChip and Illumina BeadArray.Â This paper aims to give an overview about microarray technology on the two platforms and the advantage of using them on bioinformatics research.